Analisis Implementasi Sistem Manajemen Keselamatan dan Kesehatan Kerja Di Rumah Sakit Batara Siang Kabupaten Pangkep Tahun 2019 - Purnama Putri Syamsuddin; Haeruddin; Suharni (Program Pascasarjana Universitas Muslim Indonesia, 2020)
Background: Analysis of Implementation of the Occupational Safety and Health Management System at Batara Siang Hospital in Pangkep Regency 2019. Objective: This study aims to analyze the implementation of the work safety system in planning, inspection and corrective actions on work tools, work materials and PPE in Batara Siang Hospital in Pangkep Regency.Methods:The research method is descriptive analysis which is an approach that explores knowledge, attitudes and actions of hospital management in planning, examining and improving work tools, work materials and PPE in carrying out occupational safety and health in Batara Siang Hospital in Pangkep Regency through interviews in-depth (indepth interview) and observation (observation). Result: The results showed that the Batara Lunch School in Pangkep had applied it. Planning, checking and remedial actions for work materials in occupational safety and health standards have been carried out. Planning, examination and corrective actions for PPE have been carried out.Conclusion: batara siang hospital in Pangkep district has carried out occupational safety and health, working tools, work materials and PPE